A role of genetic studies in aggravated obstetric history: a clinical observation - Ju. E. Dobrokhotova (Акушерство, гинекология и репродукция)
Primary health care specialists play one of the defining roles in shaping treatment and diagnostic strategy by attracting colleagues from related specialties, including those dealing with medical genetic counseling. At the current stage, additional examinations allow to implement a patient-oriented integrated approach. Genetic studies can substantially improve quality of diagnostics and should be more actively used in primary care. This confirms the clinical observation using extended diagnostic tactics in the patient with non-specific complaints and a burdened obstetric history.